The cycle of violence: effects of violence experience, behavior, and attitudes on adolescents’ peer rejection networks - Favre, Céline A.; Garrote, A.; Kassis, W.; Bacher, J.; Wullschleger, A.; Aksoy, D. (Frontiers in Education, 2024)
Previous research on adolescent peer networks has mainly focused on friendship networks and their association with violence, but very limited research is available on peer rejection networks. This lack of knowledge hinders the effectiveness of preventing peer rejection and its negative effects (Laninga-Wijnen and Veenstra, 2021). Based on the theory of the cycle of violence (Widom, 1989a(Widom, , 1989b)), the present study examines the extent to which parental physical abuse experiences, aggressionaggressive behavior toward peers and acceptance of violence are related to peer rejection networks at school. Social network analysis with a stochastic actor-oriented model of longitudinal data collected from high school students (Wave 1, n = 620; Wave 2, n = 590) confirms that adolescents who frequently use aggression toward their peers are more likely to be rejected, especially if those adolescents have experienced abuse. Similarly, peers are more likely to reject adolescents with high levels of accepting violence. The results also show that aggression towards peers generally tends to decrease over time but not for adolescents who reject a larger number of students. For students who reject many peers, aggression frequency increases. From the perspective of resilience theory, peer rejection, when combined with aggression toward peers and acceptance of violence, particularly in female adolescents, creates a significant risk factor for socio-emotional development. Therefore, tackling violence attitudes, experiences and behavior in the school environment and at home is crucial in overcoming the cycle of violence.